Characteristics of Epstein–Barr viraemia in adult liver transplant patients: A retrospective cohort study. (24th May 2014) - Halliday, Neil; Smith, Colette; Atkinson, Claire; O'Beirne, James; Patch, David; Burroughs, Andrew K; Thorburn, Douglas; Haque, Tanzina
Summary Therapeutic immunosuppression following solid organ transplantation increases the risk of Epstein–Barr (EBV) viraemia, which is implicated in post‐transplant lymphoproliferative disease (PTLD). We retrospectively analysed the incidence of EBV viraemia and clinical outcomes in 98 liver transplant recipients. Patients underwent EBV DNA monitoring by whole‐blood PCR: EBV levels were correlated with clinical parameters and outcomes for a median of 249 days. 67% patients developed EBV viraemia (EBV DNA ≥100 copies/ml) and 30% had sustained viraemia. There was a trend towards higher hazard ratios for viraemia with exposure to aciclovir (HR 1.57, P = 0.12) or in recipients of a poorly HLA‐matched graft (HR 1.62, P = 0.10). These associations became significant in the subgroup with >90 days surveillance; HR 2.54 (P = 0.0015) for aciclovir and HR 1.99 (P = 0.03) for poorly matched grafts. The converse was true with ganciclovir (HR 0.56 P = 0.13). Viraemia was more prolonged in men (median duration 7 days vs 1; P = 0.01) and in those with lower UKELD scores (11 days vs 1 day; P = 0.001) but shortened with ganciclovir exposure (P = 0.06). Younger patients were more likely to have high peak viral loads (P = 0.07). No clinical signs or symptoms or adverse outcomes were associated with EBV reactivation.